DEVELOPMENT OF THE INSTITUTIONAL ENVIRONMENT FOR FINANCING HIGH-TECH ENTERPRISES IN UKRAINE - KASHUBA, Leonid (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the development of the institutional environment for financing high-tech enterprises in Ukraine and substantiates approaches to its improvement, taking into account international experience. The author defines the institutional environment as a set of state, market, and regulatory mechanisms that provide comprehensive support for innovative projects and enterprises, including legislative and regulatory acts, state programs, financial institutions, certification and consulting organizations, as well as information and educational resources. A systematic analysis of state and international programs, venture and banking financing mechanisms, accelerators, clusters, and educational initiatives contributing to the development of the high-tech sector is conducted. The current state of the institutional environment in Ukraine is investigated, in particular the development of the regulatory framework, the functioning of financial institutions, certification structures, and information and educational platforms, and the main barriers and constraints to attracting investment are identified. Based on an analysis of international experience in Germany, France, Great Britain, and Japan, recommendations are proposed for further improvement of national mechanisms for supporting innovative businesses, including expanding tax incentives, creating specialized financial structures and startup support, developing innovation clusters and accelerators, as well as actively involving international partners and investors. The conclusions emphasize the importance of an integrated approach, in which state initiatives, financial institutions, certification bodies, and the information and educational component interact with each other, ensuring effective financing of high-tech enterprises even in challenging socio-economic conditions and during martial law. The proposed recommendations aim to improve the institutional environment for financing high-tech enterprises, enhance the competitiveness of Ukrainian startups and scientific and technological companies at both national and international levels, and foster a sustainable innovation ecosystem.